2022
DOI: 10.1111/jai.14319
|View full text |Cite
|
Sign up to set email alerts
|

Age, growth, mortality, and yield‐per‐recruit of red spotted grouper Epinephelus akaara in the central Seto Inland Sea, Japan

Abstract: The red spotted grouper Epinephelus akaara is important for commercial and recreational fishing in the coastal waters of East Asia. In Japan, approximately 850,000 juveniles are released annually for stock enhancement, and the catch in several release areas has increased. Life-history traits are important for fisheries management and stocking programmers. The age, growth, and mortality of fish collected from the central Seto Inland Sea from June 2012 to November 2014 were examined using 1022 sectioned sagittal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…These findings indicate that the main spawning season of red‐spotted groupers living on the coast of Korea is from July to September, the summer season. In addition, according to a recent study by Yamamoto and Kobayashi (2017), it was reported that the spawning season of red‐spotted grouper caught in Sato Inland, Japan is from June to August. We conducted experiments using artificially cultured female red‐spotted groupers that were not collected in nature, and we investigated annual changes in the GSI and ovarian developmental phase in a fish farm environment.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that the main spawning season of red‐spotted groupers living on the coast of Korea is from July to September, the summer season. In addition, according to a recent study by Yamamoto and Kobayashi (2017), it was reported that the spawning season of red‐spotted grouper caught in Sato Inland, Japan is from June to August. We conducted experiments using artificially cultured female red‐spotted groupers that were not collected in nature, and we investigated annual changes in the GSI and ovarian developmental phase in a fish farm environment.…”
Section: Discussionmentioning
confidence: 99%
“…See, for instance, fig. 6 presented in Yamamoto and Katayama (2022) for an example of a severely righttruncated descending limb in which Z may rather be overestimated from using the LR method. Although Chapman and Robson (1960) have originally suggested such practice, Smith et al (2012) later recommended that no data truncation should be applied.…”
Section: Truncating Low Counts At Old Agementioning
confidence: 99%
“…(2021), Anderson et al . (2022), Tsai and Huang (2022), Yamamoto and Katayama (2022), Andrade et al . (2023), He et al .…”
Section: The Problemmentioning
confidence: 99%